2015
DOI: 10.1161/circulationaha.114.015177
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Rupture or Dissection in Descending Thoracic Aortic Aneurysm

Abstract: A neurysm of the descending thoracic (DTA) and thoracoabdominal aorta (TAA) is a life-threatening disorder given the risks of aortic dissection (AD) or rupture and their associated high mortality and morbidity once complications occur. The decision to intervene prophylactically, however, is complicated by the significant mortality and morbidity associated with surgical intervention for these conditions. Current practice guidelines call for surgical repair of asymptomatic thoracic aortic aneurysms with diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 27 publications
3
61
1
2
Order By: Relevance
“…Only 16% of this subgroup were free of these events over a median of 14 months. 5 These results are consistent with older studies that led to the current guidelines.…”
Section: Article See P 1620supporting
confidence: 90%
See 1 more Smart Citation
“…Only 16% of this subgroup were free of these events over a median of 14 months. 5 These results are consistent with older studies that led to the current guidelines.…”
Section: Article See P 1620supporting
confidence: 90%
“…4 However, advances in anesthesiology, endovascular repair, open surgical repair, and imaging warrant a serious look at the validity of the current guidelines. The observational study by Kim et al 5 in this issue of Circulation is therefore appropriate and worthy of attention. The authors identified patients with descending thoracic/thoracoabdominal aortic aneurysms from a database in their specialty service at their institution.…”
Section: Article See P 1620mentioning
confidence: 99%
“…Consequently, expert consensuses and opinions recommend replacement at 60 mm for an open surgical approach and 55 mm for TEVAR, assuming that endovascular treatment enables less operative morbidity and mortality [31,32,33]. Data from the IRAD registry [34] as well as a recent study by Kim et al [35] suggested 59.9-81.6% fail guidelines and dissect at smaller diameters; however, they also evaluated size after the onset of dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Consideration should, therefore, be given to lowering the threshold for intervention, particularly if less invasive endovascular approaches are feasible. 11 However, there are limited natural history data on chronic dissection of the descending aorta and the thoracoabdominal aorta to support clinical criteria for timely intervention. Elefteriades et al 12 suggested that patients with chronic aortic dissection should be treated when the aorta reaches 6 cm in diameter, similar to the value for which treatment is recommended in patients with arteriosclerotic descending thoracic aortic aneurysms.…”
Section: Stanford Classificationmentioning
confidence: 99%